2000
DOI: 10.1108/13522750010322089
|View full text |Cite
|
Sign up to set email alerts
|

Recognising deductive processes in qualitative research

Abstract: States that there are two general approaches to reasoning which may result in the acquisition of new knowledge: inductive reasoning commences with observation of specific instances, and seeks to establish generalisations; deductive reasoning commences with generalisations, and seeks to see if these generalisations apply to specific instances. Most often, qualitative research follows an inductive process. In most instances, however, theory developed from qualitative investigation is untested theory. Both quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
260
0
21

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(314 citation statements)
references
References 13 publications
1
260
0
21
Order By: Relevance
“…In a case study the researcher has less control over occurrence, and the focus remains on contemporary phenomenon in line with real-life context. Hyde (2000) explained that qualitative methods seek to recognize the core notions and effort to find the associations between variables. The qualitative data method comprehends the transcripts of interviews or observation.…”
Section: Methodsmentioning
confidence: 99%
“…In a case study the researcher has less control over occurrence, and the focus remains on contemporary phenomenon in line with real-life context. Hyde (2000) explained that qualitative methods seek to recognize the core notions and effort to find the associations between variables. The qualitative data method comprehends the transcripts of interviews or observation.…”
Section: Methodsmentioning
confidence: 99%
“…An abductive approach is described as an attempt "to compare alongside…to show side by side" (Kovách & Spens, 2005) and can be viewed through intuition or as a kind of a systematized creativity to create "new" knowledge in research process (Andreewsky & Bourcier, 2000) through several cycles of interaction between researchers, theory and data using the benefits from both inductive and deductive approach (Kovách & Spens, 2005). In an inductive approach, data about the researched phenomenon guide the analysis process, while in a deductive approach, the analysis is theoretically derived (Hyde, 2000), whereas in abductive analysis, the key element is the interaction between the theory and the data to acquire new knowledge about the phenomenon. The researcher creates a framework of different theories together with the data in a creative process of "theory matching".…”
Section: Discussionmentioning
confidence: 99%
“…As (Hyde, 2000) suggested that many social scientists and researchers are now agreed to the view that both the qualitative and quantitative methods can be used for a valid research. Similarly, (EasterbySmith et al, 1991) proposed that many researchers who took up a mix of qualitative and quantitative approaches are a balanced proposition of any type of research.…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
“…Similarly, (EasterbySmith et al, 1991) proposed that many researchers who took up a mix of qualitative and quantitative approaches are a balanced proposition of any type of research. Hence, it is not a question of which method should be used for reasoning either induction or deduction sometimes both are required for research attempts and using any one of those could be objectionable (Hyde, 2000).…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
See 1 more Smart Citation